Topic Modelling Application for Determining Competitiveness Factors of the Small Business Firms - Muhammad Masyhuri (International Journal of Social Science and Business, 2022)
Small and medium enterprises play an important role worldwide, in both developed and developing countries. A big part of the problem of small businesses today is competing and maintaining their business among competitors. This study aims to generate a theme of competitiveness from textual data by introducing topic modelling as a research approach. This type of research is quantitative research. This study uses a quantitative approach and descriptive analysis using the Mallet Topic Modelling program as an analytical tool. Ten themes have been identified, including two topics Understanding Entrepreneurship and Entrepreneurship Networks; and Conditions of Industry and Learning Organizations have the highest proportion of topic composition. These topics are used to understand the competitive factors between internal and external small businesses. This study uses the Mallet Topic Modelling Tool program, and ten factors of small business competition can be identified. The results of this study can provide a new area for future research directions. At the same time, entrepreneurs and business people can obtain competitive factors suitable for their business s sustainability.